Performance of Zakat Institutions: Strategies for Using Financial Technology to Increase Zakat Collection - Fadilah, Sri; Fitriah, Epi; Maemunah, Mey; Fauziah, N. Eva; Lestari, Rini; Rosdiana, Yuni (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study aims to analyze the strategies of Zakat institutions in adopting financial technology to optimize ZIS collection. The recognition of the significant potential of the Zakat funds has yet to be fully realized, forming a backdrop for this research. This indicated that the efficiency of the zakat collection did not reach its maximum potential. Various factors contribute to this situation, including challenges in adopting and implementing financial technology, particularly through financial technology (Fintech). Numerous hurdles hinder the effective utilization of financial technology by Zakat institutions. Conversely, embracing and incorporating Fintech, offers various advantages, such as enhancing Zakat governance and optimizing collection processes. Consequently, it is crucial to investigate how zakat institutions respond to financial technology to enhance zakat collection. This research employs a case study methodology and a descriptive analysis research approach, focusing on LAZ Rumah Zakat. The data collection involved documentation and interviews. The findings of this study indicate that the implementation of fintech in LAZ Rumah Zakat is very much needed to support the zakat collection strategy, especially with the use of social media and other technology media. Especially the rapid use of technology as an impact of the COVID-19 pandemic in 2020 and 2021.